Kajian Kritis Kitab-kitab Ulumul Hadis yang Digunakan di Pesantren: Relevansi dan Tantangannya di Era Digital - Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2024)
The classical texts of Ulumul Hadith (Sciences of Hadith) remain a fundamental component in Islamic education at Indonesian pesantren (Islamic boarding schools). Books such as Muqaddimah Ibn al-Salah, Tadrib al-Rawi, and Nukhbat al-Fikar are still widely used as primary references in the teaching of hadith sciences across both traditional and modern pesantren. However, the relevance of these texts in addressing the challenges of the digital age—such as open access to information, changing learning styles among students, and the emergence of technology-based sources—has not been critically examined. This article aims to critically analyze the content, methodology, and pedagogical approach of the Ulumul Hadith books commonly used in pesantren and assess their current relevance and effectiveness in contemporary digital learning environments. Using a descriptive qualitative approach, this study combines literature review and limited participatory observation in selected pesantren in Central and East Java. The findings show that although these classical texts offer rich academic value, they face substantial challenges in terms of presentation, digital accessibility, and the growing gap between traditional teaching methods and the expectations of a digitally native generation of students. Therefore, reinterpretation and digitalization efforts are necessary to sustain the relevance and continuity of Ulumul Hadith studies within pesantren amidst the tide of technological and educational transformation.